THE CURRENT STATUS OF ANTIBIOTIC RESISTANCE OF BACTERIAL STRAINS ISOLATED FROM RESPIRATORY SPECIMENS AT HOSPITAL A, THAI NGUYEN PROVINCE IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To identify bacterial etiologies and antimicrobial resistance patterns of bacterial strains isolated from respiratory specimens at Thai Nguyen A Hospital.Materials and Methods: A cross-sectional descriptive study was conducted on 381 culture-positive respiratory specimens collected from patients with clinical signs of respiratory infection between January 2025 and December 2025 at the Microbiology Department of Thai Nguyen A Hospital. Samples were selected using convenience sampling. Data were processed and analyzed using STATA version 14. This retrospective study was approved by Thai Nguyen University of Medicine and Pharmacy and Thai Nguyen A Hospital.Results:  Haemophilus influenzae showed a high resistance rate to ampicillin (94.3%) and cefuroxime (78.8%) but remained highly susceptible to ceftriaxone (98.1%) and levofloxacin (100%). Streptococcus pneumoniae exhibited high resistance to erythromycin (97.2%) and azithromycin (95.7%), while showing moderate susceptibility to penicillin (47.2%) and high susceptibility to levofloxacin (98.1%). Staphylococcus aureus demonstrated complete resistance to penicillin (100%) and high resistance to erythromycin (76.2%); however, high susceptibility rates were observed for linezolid (90%) and trimethoprim/sulfamethoxazole (85.7%). Pseudomonas aeruginosa showed resistance to ceftazidime (77.8%) and piperacillin–tazobactam (66.7%), with a susceptibility rate of 38.9% to amikacin.Conclusion:  These findings highlight the need to strengthen periodic antimicrobial resistance surveillance, promote rational antibiotic use based on antibiogram results, enhance hospital infection control measures, and develop treatment guidelines tailored to local bacterial epidemiology to limit the spread of antimicrobial-resistant bacteria.
Keywords: bacteria, antibiotic resistance, respiratory specimens